Pengaruh Sistem Pembayaran Asuransi Kesehatan BPJS Terhadap Akuntansi Pendapatan Rumah Sakit (Studi Pada RS PKU Muhammadiyah Gamping) - Muhammad Rifandi; Prima Shofiani (STIE Mandala Jember, 2019)
The purpose of this study was to analyze the effect of BPJS health insurance payments on accounting for hospital income. The study was conducted at the PKU Muhammadiyah Gamping hospital. This study uses a qualitative approach, data obtained from interviews, observation and documentation. The results showed that PKU Muhammadiyah Gamping hospitals implemented a BPJS health insurance payment system in the form of a prospective and retrospective combination. The existence of this BPJS payment system method has an impact on accounting for hospital income where cash inflows are delayed, however, PKU Muhammadiyah Gamping hospitals can overcome this by setting aside reserve funds that have been budgeted at the beginning of each year. Therefore the PKU Muhammadiyah Gamping hospital does not experience continuous losses due to differences in BPJS health insurance rates.